Implementation of the Direct Instruction Learning Model on 8th Grades Social Sciences Learning Outcomes at SMPN 2 Larangan - Abd. Maghni Ad-Dhahil (Business Finance Analyst Co., 2023)
This research aims to determine the implementation of the direct instruction learning model on the learning outcomes of grade 8 students at SMPN 2 Prohibition in social studies subjects and analyze the obstacles and solutions. This research uses a qualitative approach with the type of field research. The data sources obtained are based on the results of observations, interviews and documentation. Checking the validity of the data uses extended observations, as well as persistence of observations and triangulation. For data analysis, we used three techniques, namely checking data, organizing (grouping), conclusion drawing/verification (drawing conclusions). The research results show that at SMPN 2 Larangan the direct instruction learning model is implemented. In its application the teacher combines learning methods, such as; lecture, discussion and problem solving methods. Then, in implementing this direct instruction learning model, there are several obstacles. Among others; obstacles that exist for students and obstacles that exist for teachers. The obstacle for students is the difference in students' IQ levels so that the process of understanding the material takes quite a long time. Then the obstacles that exist for teachers include; (1) The teacher must understand the material in detail. (2) Teachers must be creative in choosing learning methods, taking into account that these methods must be appropriate to the learning material.